Dental fear and its effect on health behaviour of adult patients in Lodz region - Sopińska, Katarzyna; Bołtacz-Rzepkowska , Elżbieta (Journal of Stomatology, 2016)
Introduction.Despiteincreasinglysophisticated methods of treatment, fear connected with dental treatment is a common phenomenon. According to the literature, 16% to 24% of patients suffer from dental fear in different populations. Aim of the study. To assess the prevalence of dental fear and its effect on dental health behaviour among adult patients in the region of Lodz. Material and methods. The survey included 499 patients who were referred in the period of November-December 2015. The questionnaire consisted of fourteen questions and was divided into three sections: socio-demographic data, oral hygiene habits and past experience during dental treatment, and dental anxiety using the Modified Dental Anxiety Scale (MDAS). Results. The mean MDAS value in the study group was 10.9±4.79. The majority of respondents (79%) demonstrated a low or moderate level of dental anxiety. A high level of anxiety was observed in 21% of patients including 11% with dentophobia. A statistically significant correlation was found between the mean MDAS values and sex (p=0.028), age (p<0.0005), place of residence (p=0.014), socioeconomic status (p=0.038), subjective assessment of the oral health (p<0.0005), frequency of dental appointments (p<0.0005), and the negative dental experiences in the past (p<0.0005). No correlation between anxiety and education or oral hygienic habits was observed. Conclusions. According to the study, most respondents did not feel any special fear before dental treatment, every fourth person had a high level of anxiety, and every tenth person suffered from dentophobia. Clinicians should be aware of the common occurrence of fear, and try to establish a rapport with the patient based on trust.